Effect of mechanical vibration stress in cell culture on human induced pluripotent stem cells - Kanie, Kei (Regen Ther, 2019)
The development of induced pluripotent stem cell (iPSC) techniques has solved various limitations in cell culture including cellular proliferation and potency. Hence, the expectations on wider applications and the quality of manufactured iPSCs are rapidly increasing. To answer such growing expectations, enhancement of technologies to improve cell-manufacturing efficiency is now a challenge for the bioengineering field. Mechanization of conventional manual operations, aimed at automation of cell manufacturing, is quickly advancing. However, as more processes are being automated in cell manufacturing, it is need to be more critical about influential parameters that may not be as important in manual operations. As a model of such parameters, we focused on the effect of mechanical vibration, which transmits through the vessel to the cultured iPSCs. We designed 7 types of vertical vibration conditions in cell culture vessels using a vibration calibrator. These conditions cover a wide range of potential situations in cell culture, such as tapping or closing an incubator door, and examined their effects by continuous passaging (P3 to P5). Detailed evaluation of cells by time-course image analysis revealed that vibrations can enhance cell growth as an early effect but can negatively affect cell adhesion and growth profile after several passages as a delayed effect. Such unexpected reductions in cell quality are potentially critical issues in maintaining consistency in cell manufacturing. Therefore, this work reveals the importance of continuous examination across several passages with detailed, temporal, quantitative measurements obtained by non-invasive image analysis to examine when and how the unknown parameters will affect the cell culture processes.